POTENCY OF CHITOSAN AS HEAVY METAL ADSORBENT FROM INDUSTRIAL WASTE EXPOSURE - Sakinah Sakinah (Fakultas Kedokteran Universitas Lampung, 2014)
Nowadays, industries in Indonesia show progressing, such as chemistry, textile, home industry, agriculture, and others. It aims to increase prosperity of society, but it produce side products, an industrial waste. Industrial waste has negative effects to environment and human’s life. Chemistry materials that used in metal industries are toxic, which is dangerous for human’s health, not only industrial employee, but also society around the company. Exposure of metal industrial waste cause many effects to body’s organs, such as neurology, kidney function, reproduction, hemopoietic, cardiovascular and respiratory system. To solve this problem, many industries have use electrocoagulation-flotation system. Actually, high cost to coagulation and floculan, need high electricity, oxidation effect, depents on electric voltage and also it cannot used for manage high electrolyte fluid. So, many researchers have found other methods for efective metal adsorbent, one of the methods is chitosan. Chitosan has good characteristic to absorp and clot. This compound is used as an absorban heavy metal from industrial waste. Chitosan has amino group and hydroxyl which has high chemical reactivity, and cation polielectrolit to exchange the ion. So, it binds and clots the dangerous metal ion in human’s body. [J Agromed Unila 2014; 1(1):77-81] Key word: chitosan, heavy metal adsorbent, metal industrial waste